Application of BLUP in prediction of breeding values and estimation of SNP effects in dairy cattle - Ahmad, Sausan (2011)
Genetic selection for higher milk production has unavoidably resulted in a decline in fertility of dairy cattle in the UK due to the antagonistic correlation existing between fertility and milk yield. This trend in fertility has necessitated broadening the breeding programme to include fertility traits. However, the heritability of fertility traits currently used in the UK are of low heritability (h2<0.05). Therefore, one approach is to use molecular markers in order to identify animals with the highest genetic merit for fertility.